2002
DOI: 10.1037/1099-9809.8.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Why can't we just get along? Interpersonal biases and interracial distrust.

Abstract: The authors review a series of studies that illustrate how one form of contemporary racial bias of Whites, aversive racism, can shape different perspectives of Blacks and Whites in ways that can undermine race relations. This research demonstrates that contemporary racism among Whites is subtle, often unintentional, and unconscious but that its effects are systematically damaging to race relations by fostering miscommunication and distrust. In particular, the authors examine the effects of aversive racism on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
426
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(446 citation statements)
references
References 42 publications
14
426
1
5
Order By: Relevance
“…Some research suggests that dissimilarity leads to a number of negative job outcomes, including interpersonal tension and conflict (Dovidio, Gaertner, Kawakami, & Hodson, 2002) and reduced cognitive resources (Richeson, Trawalter, & Shelton, 2005). Moreover, racial dissimilarity has also been linked with increased perceptions of ethnic discrimination (Avery, McKay, & Wilson, 2008) and ultimately, reduced commitment to the A Socioecological Approach 8 organization (Tsui, Egan, & OÕReilly, 1992).…”
Section: Ethnic Dissimilarity and Job Attitudesmentioning
confidence: 99%
“…Some research suggests that dissimilarity leads to a number of negative job outcomes, including interpersonal tension and conflict (Dovidio, Gaertner, Kawakami, & Hodson, 2002) and reduced cognitive resources (Richeson, Trawalter, & Shelton, 2005). Moreover, racial dissimilarity has also been linked with increased perceptions of ethnic discrimination (Avery, McKay, & Wilson, 2008) and ultimately, reduced commitment to the A Socioecological Approach 8 organization (Tsui, Egan, & OÕReilly, 1992).…”
Section: Ethnic Dissimilarity and Job Attitudesmentioning
confidence: 99%
“…As a case in point, in the American Army Dovidio, Gaertner, Kawakami and Hodson (2002) reported the opposite. In that study it was reported that white-black power struggles are rife and that only thirty nine percent of blacks (compared with sixty eight percent of whites) reported their race relations and circumstances as a good experience.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, trust allows the individuals to take the risk of being vulnerable and to make conciliatory initiatives to the other side, with some degree of assurance that they will not be exploited (Dovidio, Gaertner, Kawakami, & Hodson, 2002). A number of studies found that increased trust toward outgroup members or their leaders is a necessary precursor of forgiveness (see Hewstone et al, 2008).…”
Section: Intergroup Trust In Conflictual Settingsmentioning
confidence: 99%